Greater Pre-Stimulus Effective Connectivity from the Left Inferior Frontal Area to other Areas is Associated with Better Phonological Decoding in Dyslexic Readers - Frye, Richard E.; Wu, Meng-Hung; Liederman, Jacqueline; McGraw Fisher, Janet (Frontiers in Systems Neuroscience, 2010)
Functional neuroimaging studies suggest that neural networks that subserve reading are organized differently in dyslexic readers (DRs) and typical readers (TRs), yet the hierarchical structure of these networks has not been well studied. We used Granger Causality (GC) to examine the effective connectivity of the preparatory network that occurs prior to viewing a non-word stimulus that requires phonological decoding in 7 DRs and 10 TRs who were young adults. The neuromagnetic activity that occurred 500 ms prior to each rhyme trial was analyzed from sensors overlying the left and right inferior frontal areas (IFA), temporoparietal areas (TPA), and ventral occipitotemporal areas (VOTA) within the low, medium, and high beta and gamma sub-bands. A mixed-model analysis determined whether connectivity to or from the left and right IFAs differed across connectivity direction (into vs. out of the IFAs), brain areas, reading group, and/or performance. Results indicated that greater connectivity in the low beta sub-band from the left IFA to other cortical areas was significantly related to better non-word rhyme discrimination in DRs but not TRs. This suggests that the left IFA is an important cortical area involved in compensating for poor phonological function in DRs. We suggest that the left IFA activates a wider-than usual network prior to each trial in the service of supporting otherwise effortful phonological decoding in DRs. The fact that the left IFA provides top-down activation to both posterior left hemispheres areas used by typical readers for phonological decoding and homologous right hemisphere areas is discussed. In contrast, within the high gamma sub-band, better performance was associated with decreased connectivity between the left IFA and other brain areas, in both reading groups. Overly strong gamma connectivity during the pre-stimulus period may interfere with subsequent transient activation and deactivation of sub-networks once the non-word appears.